2017
DOI: 10.1042/cs20160642
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal nitric oxide synthase-derived hydrogen peroxide effect in grafts used in human coronary bypass surgery

Abstract: Recently, HO has been identified as the endothelium-dependent hyperpolarizing factor (EDHF), which mediates flow-induced dilation in human coronary arteries. Neuronal nitric oxide synthase (nNOS) is expressed in the cardiovascular system and, besides NO, generates HO The role of nNOS-derived HO in human vessels is so far unknown. The present study was aimed at investigating the relevance of nNOS/HO signaling in the human internal mammary artery (IMA) and saphenous vein (SV), the major conduits used in coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
0
5
0
3
Order By: Relevance
“…A recent study by Endlich et al . () provided pharmacological evidence for the generation of H 2 O 2 by nNOS. Another notable study by Ihara et al .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Endlich et al . () provided pharmacological evidence for the generation of H 2 O 2 by nNOS. Another notable study by Ihara et al .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a study evaluating human internal mammary artery and saphenous veins undergoing coronary artery bypass grafting, showed that H 2 O 2 – considered an endogenous EDH mechanism in the coronary bed – induced different responses in arteries and veins [ 108 ]. While H 2 O 2 was produced by the nNOS on the internal mammary artery, resulting in vasodilation after acetylcholine stimuli; in saphenous veins H 2 O 2 was generated by nNOS and by COX, inducing venoconstriction [ 108 ].…”
Section: Venous System In Heart Failurementioning
confidence: 99%
“…Последний играет важную роль в регуляции взаимодействия клеток между собой и с экстрацеллюлярным матриксом и способен вовлекать в процесс ремоделирования сосудистой стенки адвентициальные миофибробласт-подобные клетки. Авторы указанного исследования продемонстрировали, что посредством этого белка изменения изначально происходят в адвентиции, в частности в зоне vasa vasorum, позже в медиальном слое [4].…”
Section: аналитический обзорunclassified
“…Так, в литературе неоднократно описано, что некоторые кондуиты, в частности внутренняя грудная артерия, оказывают особое кардиопротективное действие. В силу способности продуцировать ряд веществ, таких как оксид азота, простациклин и эндотелиальный гиперполяризующий фактор [2][3][4], эти кондуиты способствуют формированию особой регуляции сосудистой стенки КА [2,5]. В целом можно предполагать о создании не только новых гемодинамических условий для перфузии коронарного русла, но и, по всей вероятности, нового иммунно-биохимического и даже молекулярно-генетического комплекса факторов [1,6].…”
Section: Introductionunclassified